Nutritional profile and immunomodulatory potential of a polyherbal honey formulation for stunted children - Akrom Akrom; Titiek Hidayati; Arif Budi Setianto; Laela Hayu Nurani; Ikhwan Dahlan Rais; Nurkhasanah Nurkhasanah; Lukman Hardia; Prasasti Bintarum; Muslih Anwar (International Journal of Public Health Science (IJPHS), 2026)
Stunting remains a major public health challenge in Indonesia and has been linked to immune dysregulation, including increased pro-inflammatory TNF-α and reduced anti-inflammatory IL-4 activity. Nutrient-dense polyherbal supplementation may provide a complementary strategy to support nutritional status and immune function. This experimental study investigated the nutritional composition and immunomodulatory activity of polyherbal honey (PHH) formulated with curcuma xanthorrhiza, black cumin seeds, and honey. Vitamins, minerals, and bioactive constituents were characterized using laboratory assays. The immunomodulatory effects of PHH were subsequently evaluated in HTB-183 cells by measuring IL-4 and TNF-α expression after exposure to different formulation concentrations. The analysis confirmed the presence of vitamins A, C, and E; calcium and potassium; and several bioactive compounds in the PHH formulation. PHH exposure increased IL-4 expression and reduced TNF-α expression relative to untreated cells, although the magnitude of these responses varied across concentrations. These findings demonstrate that PHH contains nutritional and phytochemical constituents with potential immunomodulatory activity. Further preclinical and clinical investigations are required to determine its efficacy and safety as complementary nutritional support for children with stunting.